Ethnopharmacy Study of Suku Anak Dalam (SAD) in Muara Kilis Village, Tengah Ilir, Tebo District, Jambi Province - Perawati, Santi; Andriani, Lili; Anggresani, Lia; Ardila, Eti (Biospecies, 2019)
ABSTRACT Background: Indonesia consists of various ethnics on each island, one of which is Suku Anak Dalam (SAD) precisely on Sumatra island of Jambi Province. Each ethnic group has a variety of natural and traditional remedies. This observation was conducted from November 2017 to February 2018 in Muara Kilis Village, Tengah Ilir District, Tebo District, Jambi Province.This research purpose to determined of various disease and know the various natural resources that are used as a treatmenton Suku Anak Dalam at Muara Kilis. Method: This research type is descriptive research using qualitative method and purposive sampling for sampling technique and open-ended interview with informant using voice recording media. Results: The disease are often experienced by Suku Anak Dalam among others fever, cough, asthma, measles, gastritis, hemorrhoids, stomachaches, and allergy. To treat the disease by utilizing natural resources like plants and animals. Part of the plants used among others, leaves, sap, and fruit, while for animal parts used are bile, urine, and blood. Processing methods are pounded, boiled, grated, and fried, while the use of these ingredients by eating, drinking, bathed, and applied directly on part of sickness skin Conclusion: Based on the results that has been done there are 8 diseases that often occur and there are 5 kinds of plants and 4 animals from different genus and family that are used as traditional medicine in Suku Anak Dalam Muara Kilis Village. Keywords: (Ethnopharmacy, Suku Anak Dalam, Diseases, Natural Resources)